NMR imaging as a tool for studying the diffusion and co-diffusion of gases in zeolite catalysts - Fraissard, Jacques (Diffusion Fundamentals, 2005)
1H NMR imaging is a powerful technique for studying the diffusion of pure hydrocarbons (for example benzene and n-hexane) during their adsorption in or desorption from a fixed bed of zeolite crystallites. This technique is used to visualize the progression of the diffusing molecules in the zeolite bed and to determine their intracrystallite diffusion coefficients. More importantly, NMR imaging is today the only technique able to give the time dependence of the distribution of two gases during their competitive diffusion.